2018
DOI: 10.1103/physrevfluids.3.113101
|View full text |Cite|
|
Sign up to set email alerts
|

Material transport in the left ventricle with aortic valve regurgitation

Abstract: This experimental in vitro work investigates material transport properties in a model left ventricle in the case of aortic regurgitation, a valvular disease characterized by a leaking aortic valve and consequently double-jet filling within the elastic left ventricular geometry. This study suggests that material transport phenomena are strongly determined by the motion of the counterrotating vortices driven by the regurgitant aortic and mitral jets. The overall particle residence time appears to be significantl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
(71 reference statements)
2
14
0
Order By: Relevance
“…how long particles remain within a region of interest). In Di Labbio et al ( , 2021, we have demonstrated that the particle residence time increases monotonically from the healthy scenario through to the most severe with an important exception that the first moderate scenario (ROA = 0.059) experiences the largest residence time (66 % more than the most severe case). In figures 8, 10 and 11 of that article, we show that this case exhibits a stagnant flow region surrounding the apex of the ventricle model; however, we did not address the extent of the mixing occurring in its vicinity.…”
Section: E12-17mentioning
confidence: 88%
See 1 more Smart Citation
“…how long particles remain within a region of interest). In Di Labbio et al ( , 2021, we have demonstrated that the particle residence time increases monotonically from the healthy scenario through to the most severe with an important exception that the first moderate scenario (ROA = 0.059) experiences the largest residence time (66 % more than the most severe case). In figures 8, 10 and 11 of that article, we show that this case exhibits a stagnant flow region surrounding the apex of the ventricle model; however, we did not address the extent of the mixing occurring in its vicinity.…”
Section: E12-17mentioning
confidence: 88%
“…This generates a vortex that persists throughout the cardiac cycle, acting as the organizing centre of the flow and as a reservoir of kinetic energy (Kilner et al., 2000; Pedrizzetti & Domenichini, 2005; Wieting & Stripling, 1984). The vortex encourages ‘new’ inflowing blood to closely follow the contour of the ventricle wall, forming a channel from inflow to outflow (Charonko, Kumar, Stewart, Little & Vlachos, 2013; Di Labbio, Vétel, & Kadem, 2018; Hendabadi et al., 2013). Meanwhile, by the end of the filling phase (diastole), ‘old’ blood is organized into a column just below the aortic valve, in position to be ejected with ease (Di Labbio et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Transparent silicone (Silastic T4) was the material of choice for manufacturing of the left ventricle, aorta, and left atrium due to its desirable mechanical property and extensive use in similar research [6,[12][13][14][15]. Modeling of the left ventricle for this study was symmetrically shaped with an angle of 28 • between the inflow and outflow tract (see Figure 2) and with geometric properties as described in [3]. Changing the mitral valve orientation was achieved by sowing the valve to a 3D printed part with different angles.…”
Section: Methodsmentioning
confidence: 99%
“…The filling phase is characterized by an asymmetric jet that smoothly propagates towards the outflow tract [1,2]. The jet is not continuous; rather, it is characterized by two phases-the E wave (ventricular dilation) and the A wave (atrial contraction) [3][4][5]. The formation of a vortex ring surrounding the central jet is due to the boundary layer separation from the mitral valve leaflet, and the observed asymmetry in the ring sizes occurs because of the asymmetric nature of the mitral valve leaflets.…”
Section: Introductionmentioning
confidence: 99%
“…Another Lagrangian descriptor is the fluid Particle Residence Time (PRT), which measures the time that a fluid parcel spends in a given region. Recently LCS and PRT have been applied to study hemodynamics in the left ventricle [19,20,21,22,23,24,25] and large vessels [26,27,28,29,16,30,13,31].…”
Section: Introductionmentioning
confidence: 99%